Enhanced polyethylene glycol (PEG)-mediated protoplast transformation system for the phytopathogenic fungus, Ganoderma boninense - Lim, Fook-Hwa; Rasid, Omar Abd; Idris, Abu Seman; As'wad, Abdul Wahab Mohd; Vadamalai, Ganesan; Parveez, Ghulam Kadir Ahmad; Wong, Mui-Yun (Folia microbiologica, 2021)
The basidiomycete fungus, Ganoderma boninense, has been identified as the main causal agent of oil palm basal stem rot (BSR) disease which has caused significant economic losses to the industry especially in Malaysia and Indonesia. Various efforts have been initiated to understand the disease and this plant pathogen especially at the molecular level. This is the first study of its kind on the development of a polyethylene glycol (PEG)-mediated protoplast transformation system for G. boninense. Based on the minimal inhibitory concentration study, 60 µg/mL and above of hygromycin were effective to completely inhibit G. boninense growth. Approximately 5.145 × 107 cells/mL of protoplasts with the viability of 97.24% was successfully obtained from G. boninense mycelium tissue. The PEG-mediated G. boninense protoplast transformation using 1 µg of transformation vector, 25% of PEG solution, 10 min of pre-transformation incubation, and 30 min of post-transformation incubation has improved the transformation rate as compared with the previous reported protocols for other basidiomycete fungi. Optimization of four transformation parameters has improved the transformation efficiency of G. boninense from an average of 2 to 67 putative transformants. The presence of hygromycin phosphotransferase (hpt) and enhanced green fluorescent protein (eGFP) genes in the putative transformants was detected by PCR and verified by gene sequence analysis. Southern hybridization result further confirmed the integration of hpt gene in G. boninense transformants, and the green fluorescent signal was detected in the G. boninense transformants under the microscopic analysis. The establishment of this transformation system will accelerate the gene function studies of G. boninense especially those genes that may contribute to the pathogenesis of this fungus in oil palm.
Keywords: Protoplasts; molekulární biologie; protoplasty; Transformation, Genetic; transformace genetická; Ganoderma; polyethylenglykoly; Molecular Biology; Polyethylene Glycols